Coagulase gene and agr complex polymorphism-based genotyping of Staphylococcus aureus isolated from non-human primates - V. A. Kalashnikova (Ветеринария сегодня)
Staphylococcus aureus is a pathogenic microorganism causing a great number of diseases in humans and animals. Many researches on genotyping Staphylococcus aureus isolated from humans and mastitis affected cows are performed, but no foreign reports on typing of Staphylococcus aureus detected in monkeys have been found. Staphylococcus-induced infections are however widely spread in primates. The paper demonstrates results of molecular and genetic examination of Staphy-lococcus aureus isolated from non-human primates. The examination was based on typing of coagulase gene and polymorphic locus of arg gene that regulates expression of pathogenicity-associated genes. Structures of coagulase gene (coa) and polymorphic types of regulatory gene (agr) were studied in 145 Staphylococcus aureus isolates recovered from various monkey species. The studies resulted in singular coagulase gene fragments of four dimensions: 600, 750, 800 and 900 bps. Following AluI endonuclease restriction results Staphylococcus aureus was classified in seven different coa-types. Coagulase gene of genotype VII predominated (31.7%), genotype II was detected less frequently (9.7%). Each Staphylococcus aureus isolate is specified by a definite coagulase gene restriction profile; therefore, at least seven Staphylococcus aureus strains are currently circulating in the monkeys in the monkey facilities. Herewith, those staphylococci that bear genotype VII coagulase gene are invasive as they are isolated from various organs and pus as well as from feces and nasal cavities of the animals. Analysis of the study results demonstrated that bacteria of this species could be transmitted between different monkey species. Apart from human Staphylococcus aureus, in whose genome agrI prevails, agrIV prevailed in the isolates outlined in this paper (59.3%); agrII and agrIII were detected in 5.5 and 2.1% of the isolates, respectively.